2006
DOI: 10.1089/jir.2006.26.248
|View full text |Cite
|
Sign up to set email alerts
|

High IFN-αResponses Associated with Depletion of Lymphocytes and Natural IFN-Producing Cells During Classical Swine Fever

Abstract: During the acute phase of the viral hemorrhagic disease, classical swine fever (CSF), a severe hematologic depletion in primary lymphoid organs and depletion of peripheral blood T and B lymphocytes are observed. The onset of these pathologic events is before viremia and independent of leukocyte infection, indicating a host-mediated effect possibly through a cytokine storm. Here, we show that high serum levels of interferon- alpha (IFN-alpha) were found during this phase of CSF, detectable as early as 2 days po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
62
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 38 publications
9
62
1
Order By: Relevance
“…As a consequence of the huge amounts of DC expressing IFN-α and TNF-α in secondary lymphoid organs and blood after infection, IFN-α and TNF-α productions in serum were uncommonly high, in accordance with previous reports [36,43]. By contrast, IL-12 level remained constant in serum after infection, probably because of the high IFN-α concentration known to inhibit IL-12 production [2].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…As a consequence of the huge amounts of DC expressing IFN-α and TNF-α in secondary lymphoid organs and blood after infection, IFN-α and TNF-α productions in serum were uncommonly high, in accordance with previous reports [36,43]. By contrast, IL-12 level remained constant in serum after infection, probably because of the high IFN-α concentration known to inhibit IL-12 production [2].…”
Section: Discussionsupporting
confidence: 88%
“…We did not find any significant variation in blood pDC number, despite a jagged curve, but a strong transient decrease in spleen at 48 hpi. Altogether, these results revealed a rapid turn-over of pDC in the spleen, implying a migration of stimulated NIPC between blood and spleen, as previously demonstrated in mice [1] and hypothesized in pigs [43]. These data also showed that cDC, unlike pDC, disappeared permanently from blood after infection, preventing an efficient turn-over of these DC subset in the spleen.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations